Sliding-mode control for boost converters under voltage and load variations - Mariam K. Shehata; Hossam E. Mostafa Attia; Nagwa F. Ibrahim; Basem E. Elnaghi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Boost converters are employed in DC motors, switch-mode power supplies, and other applications. Practical implementation difficulties, reliance on variable-frequency units, and delayed dynamic responses to changes in load and voltage are the main drawbacks of different control methods for the boost converter. In this paper, two techniques were proposed with the target of controlling the boost converter to improve the efficiency of the converter's performance. The two techniques used in this paper depended on fixed-frequency mode instead of variable-frequency mode because of the demerits of the latter factor. The first technique is the sliding-mode control for the AC-DC converter to achieve power factor correction and reduce the harmonic ratio significantly while regulating the output voltage. This technique was used for the DC-DC converter to obtain a rapid dynamic response to control sudden or considerable changes in loads or input voltages with a regulated output voltage. Moreover, the two-loop cascade control is the second proposed technique for the DC-DC converter to achieve an excellent dynamic response under step loads or input voltage variations with an excellently regulated output voltage. Re-simulation results validated the proposed design approach and illustrated the proposed controller's robustness and faster response time.